Rolston, Holmes, III, 1932- (Cafaro) - Cafaro, Philip, author; Gale, publisher (Colorado State University. Libraries, 2009)
Rolston's forty year career at Colorado State University has been devoted to analyzing and advocating value in nature, especially the intrinsic value of nature. Such value generates an obligation to respect nature and to conserve it. Rolston further examines how this translates into environmental policy regarding endangered species, wilderness conservation, sustainable development, and corporate responsibility. In result, Rolston has become "the father of environmental ethics." He gave the Gifford Lectures, University of Edinburgh, was awarded the Templeton Prize in Religion, and has lectured on seven continents.
Keywords: preservation; sustainable development; wilderness; intrinsic value; contemporary philosophy; environmental philosophy; consumption; conservation; biodiversity; Rolston, Holmes, 1932-2025; instrumental value; population